We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
381
1
avatar

mx2 + 2mx = 2x − 1 − m

 Oct 12, 2017
 #1
avatar+105534 
+1

mx2 + 2mx = 2x − 1 − m

 

\(mx^2 + 2mx = 2x − 1 − m\\ mx^2 + 2mx - 2x +1+ m=0\\ mx^2 + (2m - 2) x+(1+ m)=0\\ \text{This will have at least one solution when }\triangle\ge 0\\ \triangle=b^2-4ac\\ (2m-2)^2-4m(1+m)\ge 0\\ (4m^2-8m+4)-4m-4m^2\ge 0\\ -12m+4\ge 0\\ -12m\ge -4\\ m\le \frac{1}{3} \)

.
 Oct 12, 2017

29 Online Users

avatar
avatar
avatar
avatar